The effect of a sport-based intervention to prevent juvenile delinquency in at-risk adolescents. (November 2018) - Spruit, Anouk; Hoffenaar, Peter; van der Put, Claudia; van Vugt, Eveline; Stams, Geert Jan
Abstract: Despite the wide implementation of sport-based crime prevention programs, there is a lack of empirical knowledge on the effectiveness of these interventions. This study evaluated a Dutch sport-based program in N = 368 youth at risk for juvenile delinquency. Intervention effects were tested in a quasi-experimental study, comparing the intervention group with a comparison group using multiple sources of information. The study was conducted under conditions that resemble real-life implementation, thereby enhancing the relevance of this contribution to practitioners. The primary outcome was juvenile delinquency, measured by official police data. The secondary outcomes were risk and protective factors for delinquency, assessed with self- and teacher reports. A significant effect was found on one delinquency measure. The intervention group consisted of fewer youth with police registrations as a suspect than the comparison group ( d = −0.34). We did not find an intervention effect on the number of registrations as a suspect in each group. In addition, no significant intervention effects were found on the secondary outcomes. Implications for theory and practice concerning the use of sport-based crime prevention programs are discussed. Highlights: Empirical evidence of the effectiveness of sport-based crime prevention is currently lacking. AJB is a Dutch sport-based crime prevention program for at-risk youth. This study found small, significant effects of AJB on juvenile delinquency. No effects were found on risk and protective factors for juvenile delinquency. The implementation and use of sport-based interventions should be followed critically.